Любовный сюжет в "Мастере и Маргарите" - Fast, Piotr (Przegląd Rusycystyczny, 2018)
Love story in Bulgakov’s The Master and Margarita In this paper the history of love between the protagonists of Mikhail Bulgakov’s The Master and Margharita was described as a phenomenon mirroring some conventional patterns typical of mass-audience fiction. According to the author, the above-mentioned history contains — both in its plot and in the cultural conventions it refers to — many clichés typically present in love stories being the structural core of the plot of mass-audience culture. Even the final fate of the Bulgakov’s protagonists was derived from that source being actually an idyllic culmination of the plot leading towards an emotional entropy.